KEPEMIMPINAN YANG BERBUDAYA (Studi di Desa Boti Kecamatan Kie Kabupaten Timor Tengah Selatan) - Saingo, Yakobus Adi; Se’u, Windynia G. G.; Manu, Lukas; Sette, Gusti Y.; Lopo, Yismaya D. (Studi Budaya Nusantara, 2022)
This study aims to explore in depth the concept of cultural leadership in the Boti tribe. This study uses a qualitative research design with a thematic analysis approach. The informants in this study were the leader of the boti tribe who were called "usif or king", the village head and 18 followers as well as significant others as well as one informant who knew about the Boti tribe. Data obtained through in- depth interviews, observation and documentation. The results of the study explain the existence of traits and behaviors that are born from the leader's personality and those born from culture. The main role of the leader is to protect the people and nature which is done through the tradition of planting corn. The results of the study show that the physiological impact is meeting basic needs and psychology, namely independence and self-esteem of followers. The concept of leadership in the Boti tribe also talks about the influencing process between leaders and followers. This influencing process involves the nature and behavior of the leader, as well as power i.e. spiritual ability and authority over the Boti ethnic.